Rare and endemic plant species of the flora of Kostanay Region - Perezhogin, Yu.; Borodulina, O.; Suyundikova, Zh. (Fundamental and Experimental Biology, 2026)
Based on research conducted in the territory of Kostanay Region from 1995 to 2025, eight endemic plant species belonging to five families and seven genera have been recorded in the region. Rare and endangered plant species listed in the Red Book of the Republic of Kazakhstan are represented in Kostanay Region by 18 taxa: Convallaria majalis L., Ornithogalum fischerianum Krasch., Alnus glutinosa (L.) Gaertn., Betula tianschanica Rupr., Dianthus capitatus subsp. andrzejowskianus Zapał., Drosera rotundifolia L., Chimaphila umbellata (L.) W.P.C. Barton, Lilium martagon L., Tulipa sylvestris subsp. australis (Link) Pamp., Tulipa suaveolens Roth., Nymphoides peltata (S.G. Gmel.) Kuntze, Dactylorhiza maculata subsp. fuchsii (Druce) Hyl., Epipactis palustris (L.) Crantz., Koeleria macrantha subsp. macrantha, Stipa pennata L., Adonis volgensis Stev., Pulsatilla patens (L.) Mill., Pulsatilla patens subsp. flavescens (Zucc.) Zämelis (= Pulsatilla flavescens (Zucc.) Juz.). The data were obtained through a review of literature sources and during numerous botanical expeditions conducted by the authors in the Kostanay Region. All collected specimens are deposited in the Herbarium of Kostanay Regional University (KSPI). This article presents precise locality data for endemic and rare plant species of the region, which may contribute to improving their protection and to the development of targeted conservation measures.